Developing Students' Critical Reasoning Based on Inductive Thinking Learning Models - Muflihin, Iin Yunus; Abdul Rahman, Mohd Safian Bin; Kaimudin, Kaimudin; Abidin, Zaenal; Riam, Zaenal Abidin; Maulana, Fikri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Critical reasoning is one of the essential competencies crucial for enhancing the quality of human resources. However, in reality, many students still struggle to develop critical thinking skills due to inadequate learning approaches. This study aims to develop students' critical reasoning through the implementation of the inductive thinking model, which emphasizes the reasoning process from specific observations toward general understanding. This model encourages students to actively observe, analyze, draw conclusions, and build concepts based on concrete data. The research employed a qualitative approach with a library research method. Data were collected from various scientific literatures such as journals, books, and previous relevant research on inductive learning and critical reasoning. The findings show that the application of the inductive thinking model significantly improves students' critical reasoning abilities. Active student engagement in the learning process and the teacher's role as a facilitator and discussion director are key success factors. The conclusion affirms that developing critical reasoning through the inductive approach is an effective and relevant strategy for modern educational settings. The implication is the need for innovative, student-centered learning models that foster active interaction to nurture a critically minded and solution-oriented generation. Penalaran kritis merupakan salah satu kompetensi utama yang sangat penting dalam meningkatkan kualitas sumber daya manusia. Namun, kenyataannya, banyak siswa masih kesulitan dalam mengembangkan kemampuan berpikir kritis karena pendekatan pembelajaran yang belum memadai. Penelitian ini bertujuan untuk mengembangkan penalaran kritis siswa melalui penerapan model berpikir induktif yang menekankan proses berpikir dari hal-hal khusus menuju pemahaman umum. Dengan model ini, siswa didorong untuk aktif mengamati, menganalisis, menyimpulkan, dan membangun konsep berdasarkan data konkret. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka. Data dikumpulkan dari berbagai literatur ilmiah seperti jurnal, buku, dan hasil penelitian terdahulu yang relevan dengan topik pembelajaran berpikir induktif dan penalaran kritis. Hasil penelitian menunjukkan bahwa penerapan model berpikir induktif secara signifikan dapat meningkatkan kemampuan penalaran kritis siswa. Keterlibatan aktif siswa dalam proses pembelajaran serta peran guru sebagai fasilitator dan pengarah diskusi menjadi kunci keberhasilan. Simpulan dari penelitian ini menegaskan bahwa pengembangan penalaran kritis melalui pendekatan induktif merupakan strategi yang efektif dan relevan untuk diterapkan dalam konteks pembelajaran modern. Implikasinya, dibutuhkan inovasi pembelajaran yang berpusat pada siswa dan mendorong interaksi aktif demi mencetak generasi yang berpikir kritis dan solutif.